(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The present study was undertaken to the in-vitro antioxidant properties of Vernonia cinerea and to synthesis, characterization and evaluate the biomedical application of iron nanoparticles from V. cinerea. For this V. cinerea was collected and the leaves were extracted using different solvents (ethanol, hexane, chloroform). Further the antioxidant potential of various concentrations (100 to 300µg/ml) of the extracts was performed through different standard antioxidant assays. The antioxidant potential of the extracts was compared with standard ascorbic acid. Iron nanoparticles were synthesized using V.